1992
DOI: 10.1063/1.351510
|View full text |Cite
|
Sign up to set email alerts
|

Very low-emittance solar selective surfaces using new film structures

Abstract: Articles you may be interested inLow-emittance electron bunches from a laser-plasma accelerator measured using single-shot X-ray spectroscopy AIP Conf. Proc. 1507, 278 (2012); 10.1063/1.4773707 A lowenergy and lowemittance ion beam source for use with the supermicrobeam production system (abstract) Rev. Sci.New cermet film structures suitable for selective solar absorbers, composed of two cermet sublayers with identical metal volume fractions in each sublayer, on metal reflectors with an antireflection dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 44 publications
(1 reference statement)
1
41
0
Order By: Relevance
“…Simulations indicated that the double layer cermet film exhibits a higher conversion efficiency compared with the uniform cermet or graded cermet film. 96 The double-cermet layer structure consisting of a AlN top layer, a cermet layer with a low metal volume fraction, and another cermet layer with a high metal volume fraction exhibited a high solar absorptance of 0.953 and a near-normal emittance of 0.051 for W-AlN cermet 97 and 0.933 and 0.025, respectively, for SS-AlN cermet. 98 The W-and SSAlN cermet films offer the advantage of the high reactivity of aluminum with nitrogen.…”
Section: Multilayer Absorbersmentioning
confidence: 98%
“…Simulations indicated that the double layer cermet film exhibits a higher conversion efficiency compared with the uniform cermet or graded cermet film. 96 The double-cermet layer structure consisting of a AlN top layer, a cermet layer with a low metal volume fraction, and another cermet layer with a high metal volume fraction exhibited a high solar absorptance of 0.953 and a near-normal emittance of 0.051 for W-AlN cermet 97 and 0.933 and 0.025, respectively, for SS-AlN cermet. 98 The W-and SSAlN cermet films offer the advantage of the high reactivity of aluminum with nitrogen.…”
Section: Multilayer Absorbersmentioning
confidence: 98%
“…A cermet consists of nanoscale metal particles embedded within ceramic binders [30]. Typical ceramic binder materials include alumina (Al 2 O 3 ) [41], silicon dioxide (SiO 2 ), aluminum oxynitride (AlON) [8] and zirconium dioxide (ZrO 2 ) [42]. The cermet layer by itself has strong solar absorption and high transmission in the mid-IR.…”
Section: Metal-dielectric Composite Selective Solar Absorbersmentioning
confidence: 99%
“…Since then, to achieve the spectral selectivity, various materials and structures such as the semiconductor, composite media, absorber-reflector tandem, and the materials with the rough or porous surface, cermet and multilayer films have been studied as the practical approaches for the solar selective absorber design and construction [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Among these materials and structures, the multilayer-film-based structures are of special interest because of their good spectral properties and high thermal stability [9,10], which makes them particularly suitable for the photo-thermal solar energy conversion applied under the medium and high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%